Addressing the higher education for sustainable development agenda at the College of Open and Distance Learning, St. Mary's University, Ethiopia: opportunities and challenges. Issue 1 (9th August 2021) - Tamrat, Wondwosen
Abstract : Purpose: This study aims to assess the extent to which sustainable development practices are prevalent at the College of Open and Distance Learning (CODL), St. Mary's University, Ethiopia. The assessment focused on identifying the college's inclusion of the sustainable development agenda in its policy statements, various functions and practices. Design/methodology/approach: The study adopted a mixed-method approach and used a case study in its design. Data were generated from a standard survey questionnaire, adopted from the unit-based sustainability assessment tool (Togo and Lotz-Sisitka, 2009 ), a semi-structured interview and documentary evidence. Findings: The findings revealed that CODL has limited involvement in sustainability issues despite relevant policy directions set at national and institutional levels. Current engagement patterns are limited to teaching, course provision and a few areas of operations and management while a serious gap has been noted as regard the two core functional areas of research and community service which happen to be neglected. Research limitations/implications: This study was based on a single CODL, albeit an institution with a long history of offering distance education in Ethiopia. Despite its contribution to an understanding of how sustainability issues are addressed in the context of Africa in general and Ethiopia in particular, the generalizability of the findings to other similar institutions is limited. Originality/value: There is very little research in Africa as regard the involvement of higher education institutions in promoting the issues of sustainability in general and distance education providers in particular. In addition to addressing this gap, the study suggests the need for distance education institutions to improve their mapping strategies and respond to the greater concerns of sustainable development.